Long term enhanced solid-state fermentation: Inoculation strategies for amylase production from soy and bread wastes by Thermomyces sp. in a sequential batch operation. Issue 2 (June 2016) - Cerda, Alejandra; El-Bakry, Mamdouh; Gea, Teresa; Sánchez, Antoni
Graphical abstract: Highlights: Amylases were produced by solid-state fermentation (SSF) with Thermomyces sp. Operation in sequential batches allows for a SSF maintained in time. Production of amylases was enhanced by 500% using the sequential batch operation. Fermented solids from batch are effective inoculum for amylase production. Recycling fermented solids as inoculum enhances the yield of the process. Abstract: The effect of two thermophilic amylase producing strains was evaluated using different mixtures of soy and bread wastes. Thermomyces sp. was found to be better inoculum than Geobacillus sp. for a soy and bread waste mixture (90:10 w/w respectively) producing a maximum enzyme activity of 39.9·10 3  U g −1 dry substrate. Three strategies (a, b, c) were evaluated for solid-state fermentation (SSF) operation in sequential batches. Fermented solids from each batch were used to inoculate the following batch: (a) solids at the moment of maximum biological activity; (b) final solids (end of the process, maximum amylase production); (c) final solids after enzymatic extraction. The evaluated strategies led to an increase in amylase production of 50, 500 and 98% for each strategy, respectively. This indicates the suitability of fermented solids to act as inoculum and the enhancement of amylase production compared to traditional batches. As one of the main challenges of SSF is the maintenance of a productive process along time, these results confirm SSF as an excellent option to produce amylases from organic wastes.